Characterization of a parapatric contact zone between Astrocaryum macrocalyx and Astrocaryum urostachys at the boundary of the Marañón-Pastaza flood plain and the Iquitos arch - Vargas Paredes, Víctor (2008)
This study identifies a parapatric contact zone between Astrocaryum macrocalyx and Astrocaryum urostachys at the boundary between the Marañón-Pastaza flood plain and the Iquitos Arch, in the northern Peruvian Amazon. The area sampled covers 35,5 ha in the form of 9 transects 1-3 km long × 20 m wide. All Astrocaryum individuals were recorded within the transects, and their size was measured as well as topographical data of the environment. The results show that the two species meet only in a small area in the confluence zone of Marañón and Tigre rivers near the southwest basement of the Iquitos Arch. A total of 1133 Astrocaryum individuals were recorded, mostly in the 0—3,90 m size classes, with only 9,2% of the individuals exceeding 12 m in high. Within the three topographical positions considered (slope, valley bottom and ridge), most individuals were found in the lower slopes and bottoms of valleys.